The effect of culture on accounting conservatism during adoption of IFRS in the EU. Issue 2 (8th May 2018) - Zeghal, Daniel; Lahmar, Zouhour
Abstract : Purpose: This paper aims to examine the impact of culture on accounting conservatism during transition to international standards. Design/methodology/approach: The sample used in this analysis consists of 15 countries of the European Union that have adopted International financial reporting standards (IFRS) pursuing Regulation N° 1606/2002. The study covers the 2000-2010 period. Two conservatism measures are used, theBasu (1997) measure to account for conditional conservatism and the accruals measure to account for unconditional conservatism. To test the impact of culture, the six dimensions ofHofstede (1980, 2010 ) are used. Findings: The results of the analysis show that variation of conditional conservatism is influenced by the six cultural dimensions. However, unconditional conservatism is only affected by power distance. Originality/value: The results of the study are interesting and provide a better understanding of the adoption of IFRS worldwide. The role of culture in explaining accounting practices after adopting a single set of accounting standards is particularly highlighted.